(untitled) (LACCEI, 2024)
The present research had as a general objective to determine how the proposal to improve the commercial area according to Social Marketing theory, CRM, Visual Merchandising and Network marketing influences the sales of footwear in MSE, Trujillo 2021. It began with the diagnosis of the commercial area through the application of a virtual interview. The information obtained was analyzed, and with the help of the FODA matrix and the Ishikawa Diagram, it was determined that the MSE presented economic losses in the commercial area, whose root causes were determined: low profitability of advertising, insufficient delivery service and lost sales due to excessive response time. Based on this, Digital Marketing tools were proposed: Visual Merchandising, CRM, Network Marketing, Social Media Marketing, the time study of the area’s operations and the Montecarlo simulation. Finally, it was obtained as a result that the improvement proposal was positive, obtaining an increase in sales valued at S / 424,060 and a B / C of 9.7.